Burnout Among Special Education Teachers. The role of Digital Technologies - Stathopoulou, Agathi; Vlachaki, Lamprini; Driga, Anna Maria; Loukeri, Paraskevi Ioanna (Eximia, 2022)
The present study examines the levels of burnout among special educators of students with mental retardation and the relationship among gender, age, marital status, work experience, training, initial personal career prospects and the degree of burnout experienced by teachers of mental retardation students. The survey was distributed in a sample of 64 special education teachers working with mental retardation students in public schools. The data was collected by using the Maslach Burnout Inventory (M.B.I.-E.S.). The results indicated that special education teachers experience middle levels of emotional exhaustion, low levels of depersonalization and middle levels of personal achievement. Gender, marital status, training and initial personal career prospects were found to have significant correlation with special educators burnout. In addition, the results showed that there is not significant correlation between teachers' age or work experience and the three dimensions of burnout.